Developing-country vaccine manufacturers' technical capabilities can make a difference in global immunization. Issue 36 (23rd August 2021) - Hayman, Benoit; Dennehy, Maureen
Highlights: Nine DCVMN members have COVID-19 vaccines in clinical trials. DCVMN members have strong capabilities for large-scale vaccine manufacturing. Sampled manufacturers are prepared to dedicate existing capacities to COVID-19 vaccine production. Partnerships are key for the development, production, and supply of COVID-19 vaccines. Abstract: Members of the Developing Countries Vaccine Manufacturers' Network (DCVMN) have been actively engaged in the development of COVID-19 vaccine candidates. According to the WHO COVID-19 vaccine landscape updated on 29 December 2020, 18 member manufacturers had vaccines in preclinical or clinical trials, including three members with candidates in Phase III trials. Once successful candidates have been identified there will be a need for large scale vaccine manufacturing and supply, in which DCVMN member manufacturers can play a key role. In an internal survey in 2019, DCVMN members reported the capability to supply over 3.5 billion vaccine doses annually, and the provision of over 50 distinct vaccines to 170 countries. To describe the capabilities of DCVMN member manufacturers more precisely, a 121-question survey was circulated to 41 Network members. The survey assessed the manufacturers' capabilities in utilizing various technology platforms, cell cultures and filling technologies, in addition to their capacities for manufacturing drug products. The survey also evaluated manufacturers' preparedness to dedicate existing capacities to COVID-19 vaccine production. Results revealed that sampled manufacturers have strong capabilities for manufacturing vaccines based on recombinant technologies, particularly with mammalian cells, and microbial and yeast expression systems. Capabilities in utilizing cell cultures were distributed across multiple cell types, however manufacturing capacities with Vero and CHO cells were prominent. Formulating and filling findings illustrated further large-scale capabilities of Network members. Sampled manufacturers reported that over 50% of their capacity for vaccine manufacturing could be dedicated to COVID-19 vaccine production.